PENINGKATAN HASIL BELAJAR SISWA KELAS VII SMP NEGERI TIAKUR PADA MATERI BANGUN DATAR PERSEGI PANJANG MELALUI MODEL PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) - Laurika, Elsisca Riani Sani; Laurens, Theresia; Moma, La (Program Studi Pendidikan Matematika (Kampus Kab. Maluku Barat Daya) Universitas Pattimura, 2022)
This research is a classroom action research that aims to improve the learning outcomes of flat rectangle using the Numbered Heads Together (NHT) learning model in class VIID of SMP Negeri Tiakur in the odd semester of the 2020/2021 school year with 15 students. Cycle I held 2 meetings and cycle II held 2 meetings including the final test of cycle I and cycle II. Data retrieval is done using learning outcomes test and observation sheets. The collected data were analyzed using quantitative and quality analysis. The results of this study indicate that the classical mastery learning outcomes of class VIID students of SMP Negeri Tiakur at the endof the first cycle are 46,67%. While the classical completeness value of student learning outcomes in the second cycle is 86,67%. Thus the learning outcomes of class VIID students of SMP Negeri Tiakur in cycleI to cycle II increased by 40% through the application of the Numbered Heads Together.